Changes Caused by Low Doses of Bisphenol A (BPA) in the Neuro-Chemistry of Nerves Located in the Porcine Heart - Krystyna Makowska; Slawomir Gonkowski (Animals, 2021)
Bisphenol A (BPA) contained in plastics used in the production of various everyday objects may leach from these items and contaminate food, water and air. As an endocrine disruptor, BPA negatively affects many internal organs and systems. Exposure to BPA also contributes to heart and cardiovascular system dysfunction, but many aspects connected with this activity remain unknown. Therefore, this study aimed to investigate the impact of BPA in a dose of 0.05 mg/kg body weight/day (in many countries such a dose is regarded as a tolerable daily intake–TDI dose of BPA–completely safe for living organisms) on the neurochemical characterization of nerves located in the heart wall using the immunofluorescence technique. The obtained results indicate that BPA (even in such a relatively low dose) increases the number of nerves immunoreactive to neuropeptide Y, substance P and tyrosine hydroxylase (used here as a marker of sympathetic innervation). However, BPA did not change the number of nerves immunoreactive to vesicular acetylcholine transporter (used here as a marker of cholinergic structures). These observations suggest that changes in the heart innervation may be at the root of BPA-induced circulatory disturbances, as well as arrhythmogenic and/or proinflammatory effects of this endocrine disruptor. Moreover, changes in the neurochemical characterization of nerves in the heart wall may be the first sign of exposure to BPA.